PENGARUH GAYA KEPEMIMPINAN, MOTIVASI KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT LEECO BINTANG PERKASA - Susanti; David Humala Sitorus (SCIENTIA JOURNAL, 2022)
A good leadership style is a leader must possess. Because leadership styles can be used as a way to interact employees. In a leadership that commands them to invite subordinates to perform their duties and work together to improve employee performance in the company to achieve personal and organizational goals. The purpose of this study was to analyze the impact of leadership style, work motivation and work discipline on employee performance at PT Leeco Bintang Perkasa. The independent variables used in this study are leadership style, work motivation and work discipline, while there is only one dependent variable in this study, employee performance. The study used a sample of 105 respondents drawn through a non-probabilistic sampling method. The data analysis techniques used are descriptive analysis, data quality test, data validity test, reliability test, classical hypothesis test, normality test, multicollinearity test, heteroscedasticity test, multilinear analysis test, coefficient of determination analysis hypothesis Test t-test and f-test using SPSS 25 assistance. The analysis of this study shows that leadership style has a significant impact on employee performance, work motivation has a significant impact on employee performance, employee performance has a significant impact on employees, and all variables have a positive and significant impact.